Preliminary Knowledge Analysis of First-Year Undergraduate Student at UIN Walisongo on Green Chemistry Concept - Yulia Widayanti; Siti Rahmawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
Abstract: Preliminary Knowledge Analysis of First-Year Undergraduate Student at UIN Walisongo on Green Chemistry Concept. Green chemistry is a form of application of chemistry in reducing or minimizing environmental problems. The implementation of green chemistry in education aims to increase student awareness of the environment, especially early-level students (students in semesters 1 and 3). This study aimed to analyze the knowledge of the green chemistry concept of early-level students of the Chemistry Education Study Program at UIN Walisongo Semarang. The research method used is a qualitative descriptive method. Respondents from the study were early-level students of the Chemistry Education at UIN Walisongo Semarang, totaling 52 people. The selection of respondents was based on the fact that the students of that class had already received a Chemistry Education course for Sustainable Chemistry, which included applying the concept of green chemistry. The average result of the study was 84%, with a positive response. The study results can be used as a reference for further research. Keywords: green chemistry, sustainable development, first-year undergraduate students. Abstrak: Analisis Pengetahuan Awal Mahasiswa Tahun Pertama di UIN Walisongo tentang tentang Konsep Kimia Hijau. Kimia hijau adalah bentuk penerapan kimia dalam mengurangi atau meminimalkan masalah lingkungan. Penerapan green chemistry dalam pendidikan bertujuan untuk meningkatkan kesadaran mahasiswa terhadap lingkungan, khususnya mahasiswa tingkat awal (mahasiswa semester 1 dan 3). Penelitian ini bertujuan untuk menganalisis pengetahuan konsep green chemistry pada mahasiswa tingkat awal Program Studi Pendidikan Kimia UIN Walisongo Semarang. Metode penelitian yang digunakan adalah metode deskriptif kualitatif. Responden penelitian ini adalah mahasiswa tingkat awal Pendidikan Kimia UIN Walisongo Semarang yang berjumlah 52 orang. Pemilihan responden didasarkan pada fakta bahwa siswa kelas tersebut telah mendapatkan mata kuliah Pendidikan Kimia untuk Kimia Berkelanjutan, yang termasuk dalam penerapan konsep green chemistry. Hasil rata-rata penelitian adalah 84%, dengan respon positif. Hasil penelitian tersebut dapat dijadikan sebagai acuan untuk penelitian selanjutnya. Kata kunci: kimia hijau, pengembangan berkelanjutan, mahasiswa tahun pertama.DOI: http://dx.doi.org/10.23960/jppk.v11.i1.2022.13